Ramipril and ketogenic diet response in cognitive dysfunction of insulin-resistant rats - Abdel-Kareem, Nancy M.; Elshazly, Shimaa M.; Abd El Fattah, May A.; Zaitone, Sawsan A.; Elmasry, Thanaa A.; Saleh, Asmaa; Abd El-Haleim, Enas A. (Frontiers in Pharmacology, 2025)
IntroductionHigh fructose consumption induces insulin resistance (IR), which impairs cognitive functions. Recent studies have recommended the use of ramipril for the treatment of neurological disorders. In the current study, the effects of ramipril on cognitive dysfunction were compared in IR rats fed either a ketogenic diet (KD) or normal diet (ND).MethodsFructose (10%) dissolved in drinking water was administered to the rats for 8 weeks to induce experimental IR. Ramipril (2 mg/kg daily; p.o.) was administered along with the ND or KD for an additional 5 weeks. Cognitive dysfunction was assessed at the end of the experiment using the Morris water maze (MWM) test. One-way and two-way analyses of variance (ANOVA) were used for comparisons.ResultsThe IR + ND group—as a diet control group—displayed a significant improvement in IR at the end of week 13 (1.63 ± 0.12 vs. 1.35 ± 0.06 in normal rats), as determined through the homeostasis model assessment of IR. Furthermore, brain-derived neurotrophic factors, lipid profile, insulin-degrading enzyme activities, and glycogen synthase kinase-3β activity were significantly ameliorated. The IR + KD and IR + ND + ramipril groups did not show significant improvements in most of the measured parameters compared to the normal and IR + ND groups. Notably, the IR + ND + ramipril group demonstrated significantly reduced tau protein and amyloid β (Aβ) levels. Differently, the IR + KD + ramipril group displayed ameliorated metabolic parameters (e.g., the IR index was 1.74 ± 0.13 vs. 3.34 ± 0.28 in the IR + ND + ramipril group and that of serum triglycerides (TGs) was 58.17 ± 1.85 vs. 97.5 ± 2.09 in the IR + ND + ramipril group), with no improvement in the cognitive function parameters.DiscussionRamipril may be best indicated for the treatment of KD because of its preferable peripheral and central effects. However, KD may be administered for a while as it can treat accumulated Aβ and tau proteins, and patients must be aware of its adverse effects.